2014
DOI: 10.1137/140955082
|View full text |Cite
|
Sign up to set email alerts
|

A Block Preconditioner for an Exact Penalty Formulation for Stationary MHD

Abstract: Abstract. The magnetohydrodynamics (MHD) equations are used to model the flow of electrically conducting fluids in such applications as liquid metals and plasmas. This system of non-self adjoint, nonlinear PDEs couples the Navier-Stokes equations for fluids and Maxwell's equations for electromagnetics. There has been recent interest in fully coupled solvers for the MHD system because they allow for fast steady-state solutions that do not require pseudo-time stepping. When the fully coupled system is discretize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…e.g. [13,14,16,18,21,24,[26][27][28]31] and the references therein). In [18], Gunzburger et al studied well-posedness and the finite element method for the stationary incompressible MHD equations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e.g. [13,14,16,18,21,24,[26][27][28]31] and the references therein). In [18], Gunzburger et al studied well-posedness and the finite element method for the stationary incompressible MHD equations.…”
Section: Introductionmentioning
confidence: 99%
“…Strauss et al studied the adaptive finite element method for two-dimensional MHD equations [21]. Very recently, based on the nodal finite element approximation to the magnetic field, Philips et al proposed a block preconditioner based on an exact penalty formulation of stationary MHD equations [31]. We also refer to [14] for a systematic analysis on finite element methods for incompressible MHD equations.…”
Section: Introductionmentioning
confidence: 99%
“…It may be noted that the ratio between the off‐diagonal entries in the B 12 and B 21 blocks is proportional to Ha2false/Rem2 and its large values adversely effect the system condition number. In the literature, the several block preconditioning techniques are proposed . In here, to remove the zero block in the original system, an upper triangular right preconditioner is used as follows: []center center center centerarrayB11arrayB12arrayB13array0arrayB21arrayB22array0arrayB24arrayB31array0array0array0array0arrayB42array0array0[]center center center centerarrayIarray0arrayB13array0array0arrayIarray0arrayB24array0array0arrayIarray0array0array0array0arrayI[]centerarrayrn+1arraysn+1arrayPn+1arrayqn+1=[]centerarrayd1arrayd2array0array0, which leads to []center center center centerarrayB11arrayB12arrayB11B13+B13arrayB12…”
Section: Mathematical and Numerical Formulationmentioning
confidence: 99%
“…The performance studies include the solution of systems as large as two billion unknowns using 24 000 cores . Phillips et al extended the block preconditioning techniques developed for the incompressible Navier‐Stokes equations to the stationary MHD equations in two dimensions. Cyr et al proposed and investigated the performance of several candidate block preconditioners for the incompressible resistive MHD equations and their result showed that the split approximate block preconditioner is scalable and competitive with other preconditioners, including a fully coupled algebraic multigrid method.…”
Section: Introductionmentioning
confidence: 99%
“…They investigate the performance of one-level Schwarz method and also a new fully coupled algebraic multilevel method in that paper. In [30,9,23], they explore a class of robust and scalable parallel preconditioners for Newton-Krylov solver based on the physical-based approximate block factorization (ABF) technique. They employ block factorization and approximate the resulting Schur complement recursively based on special techniques, for example, operator commutativity [12].…”
Section: Introductionmentioning
confidence: 99%